2013
DOI: 10.1007/s10103-013-1458-3
|View full text |Cite
|
Sign up to set email alerts
|

Shear bond strength of metal brackets to feldspathic porcelain treated by Nd:YAG laser and hydrofluoric acid

Abstract: Adult orthodontic treatment requires bonding orthodontic attachment to dental restorations. Ceramics are commonly used as esthetic restorative materials for the crowns and bridges. The present study evaluated the shear bond strength of metal orthodontic brackets to the feldspathic porcelain surfaces following conditioning by different powers of neodymium-doped yttrium aluminum garnet (Nd:YAG) laser and hydrofluoric acid as a conventional method. Seventy-two glazed porcelain samples were prepared and randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 19 publications
4
36
0
Order By: Relevance
“…In the current study, the SBS value of the NY group (5.11 MPa) was the lowest among the groups, which was not adequate for clinical application (6)(7)(8)(9)(10). 15 This finding is consistent with the results of Hosseini et al 33 It has been reported that a gradual increase in the output power of NY lasers improved the SBS of the bracket-to-porcelain surface. In contrast, Poosti et al 12 reported the SBS of bracket-to-porcelain surface to be 6.9 MPa, using a 0.8 W NY laser.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the current study, the SBS value of the NY group (5.11 MPa) was the lowest among the groups, which was not adequate for clinical application (6)(7)(8)(9)(10). 15 This finding is consistent with the results of Hosseini et al 33 It has been reported that a gradual increase in the output power of NY lasers improved the SBS of the bracket-to-porcelain surface. In contrast, Poosti et al 12 reported the SBS of bracket-to-porcelain surface to be 6.9 MPa, using a 0.8 W NY laser.…”
Section: Discussionsupporting
confidence: 83%
“…Numerous studies have shown that NY laser use is an effective technique for bracket adhesion. 32,33 In a recent study, an NY with a 4 W output power, 40 Hz repetition rate, and 300 lm diameter optical fiber was used for surface treatment. In the current study, the SBS value of the NY group (5.11 MPa) was the lowest among the groups, which was not adequate for clinical application (6)(7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…5,[22][23][24][25][26] It has been proven that CO 2 wavelength is absorbed almost totally by porcelain, suggesting that it as a good candidate for porcelain surface treatment. 5,28 Some investigators 5,26 used the CO 2 laser as the present study, and reported satisfying results in SBS as a result of conditioning the porcelain surface by CO 2 laser.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the efficacy of different types of lasers on porcelain surface preparation has been evaluated. 5,[22][23][24][25][26] Some studies claimed that Nd:YAG laser with appropriate parameters can be used as an alternative method for porcelain etching. 22,23 The results on the efficacy of Er:YAG laser in porcelain conditioning is more controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation